2021
DOI: 10.1038/s41598-021-01086-9
|View full text |Cite
|
Sign up to set email alerts
|

Different prognostic impact of glucose uptake in visceral adipose tissue according to sex in patients with colorectal cancer

Abstract: The purpose of this study was to investigate whether sex differences in visceral fat volume and glucose uptake measured by positron emission tomography/computed tomography (PET/CT) in abdominal visceral fat can stratify overall survival (OS) in patients with colorectal cancer (CRC). We retrospectively enrolled 293 patients diagnosed with CRC who underwent PET/CT before surgical resection. Fluorodeoxyglucose uptake of visceral adipose tissue (VAT-SUV) and subcutaneous adiposity tissue (SAT-SUV) were measured us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Since these morphological and functional modifications of adipocytes and inflammatory responses in the AT would bring qualitative changes in AT, a number of studies have tried to investigate whether the parameters of AT on diagnostic imaging examinations could represent these changes and could therefore be used as predictive factors for cancer progression [ 16 , 18 , 23 , 25 ]. On [ 18 F]FDG PET/CT, the mean SUV of visceral AT was proposed to be an imaging parameter that could reflect these qualitative changes in AT [ 16 , 18 , 23 , 26 , 27 ]. In previous studies, the mean SUV of visceral AT demonstrated significant positive associations with tumor stage and survival after treatments in patients with various intra-abdominal malignancies including colorectal cancer, gastric cancer, and pancreatic cancer [ 16 , 23 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since these morphological and functional modifications of adipocytes and inflammatory responses in the AT would bring qualitative changes in AT, a number of studies have tried to investigate whether the parameters of AT on diagnostic imaging examinations could represent these changes and could therefore be used as predictive factors for cancer progression [ 16 , 18 , 23 , 25 ]. On [ 18 F]FDG PET/CT, the mean SUV of visceral AT was proposed to be an imaging parameter that could reflect these qualitative changes in AT [ 16 , 18 , 23 , 26 , 27 ]. In previous studies, the mean SUV of visceral AT demonstrated significant positive associations with tumor stage and survival after treatments in patients with various intra-abdominal malignancies including colorectal cancer, gastric cancer, and pancreatic cancer [ 16 , 23 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…On [ 18 F]FDG PET/CT, the mean SUV of visceral AT was proposed to be an imaging parameter that could reflect these qualitative changes in AT [ 16 , 18 , 23 , 26 , 27 ]. In previous studies, the mean SUV of visceral AT demonstrated significant positive associations with tumor stage and survival after treatments in patients with various intra-abdominal malignancies including colorectal cancer, gastric cancer, and pancreatic cancer [ 16 , 23 , 26 , 27 ]. In addition to the mean SUV, we also measured the first-order and second-order textural features of perigastric AT and evaluated the relationship between these imaging features and histopathological findings, which could provide a relevant basis for using textural features of perigastric AT as imaging biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…There were 278 potentially eligible publications on post‐diagnosis adiposity and colorectal cancer outcomes. We excluded 193 publications 45–237 due to specific reasons related to the synthesis (Supplementary Table 5). Finally, 85 publications…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the presence of lymphovascular invasion and a high–high combination of rVAT and VAT-SUV were additionally significant for males. For females, any combination involving a high component of rVAT and/or VAT-SUV increased the risk of a poor OS [ 20 ].…”
Section: Discussionmentioning
confidence: 99%